Potensi Kitosan sebagai Sistem Penghantaran Gen S1 Virus SARS-CoV-2 dengan Vektor pEGFP-N1: Chitosan Potential as Delivery Agent for S1 Gene from SARS-CoV-2 with pEGFP-N1 as its Vectors - Asmarani Kusumawati; Nabilah Adzra Fahhlevi; Rarastoeti Pratiwi; Raudatul Jannah; Nurina Tahta Afwi Maulina (LPPM STIKES Guna Bangsa Yogyakarta, 2024)
Coronavirus Disease-19 (COVID-19) is a disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), this disease began to emerge at the end of 2019 and has become a pandemic to this day. Vaccination can play an important role to prevent the spread of the disease, so there are many vaccine developments, including DNA vaccines. DNA vaccines have the shortcomings of being unstable and easily degraded in vivo so it requires a delivery system such as nanoparticles. Chitosan nanoparticles are most widely used because they have the characteristics of biodegradability, low toxicity, and biocompatibility with tissues and cells. biodegradable, low toxicity, and biocompatibility with tissues and cells. The purpose of this study was to optimize and evaluate the pEGFP-N1-S1 formula with a chitosan delivery system as a DNA vaccine candidate. Recombinant plasmids were cloned in E. coli DH5α and extracted for further evaluation with restriction enzymes and sequencing. The EGFP-N1-S1 plasmid was then formulated with chitosan nanoparticles using the complex coacervation method with a mass ratio of plasmid DNA and chitosan of 1:0.1; 1:0.2; 1:0.3; 1:0.4; 1:0.5; 1:0.6 and 1:0.7. The isolated plasmid has a concentration of 2182.32 ng/L and a purity of 1.911 at absorbance ratio A260/A280 and 2.271 at A260/A230. Synthetic gene S1 (684 bp) was successfully inserted into plasmid pEGFP-N1 (4813 bp) based on the results of double digestion by BglII and EcoRI restriction enzymes and sequencing data alignment results. DNA: chitosan mass ratio of 1:0.6 is the optimal formulation for DNA to bind with chitosan perfectly.